Structural imaging studies of patients with chronic pain: an anatomical likelihood estimate meta-analysis. Issue 1 (13th January 2023) - Henn, Alina T.; Larsen, Bart; Frahm, Lennart; Xu, Anna; Adebimpe, Azeez; Scott, J. Cobb; Linguiti, Sophia; Sharma, Vaishnavi; Basbaum, Allan I.; Corder, Gregory; Dworkin, Robert H.; Edwards, Robert R.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Neuroimaging is a powerful tool to investigate potential associations between chronic pain and brain structure. However, the proliferation of studies across diverse chronic pain syndromes and heterogeneous results challenges data integration and interpretation. We conducted a preregistered anatomical likelihood estimate meta-analysis on structural magnetic imaging studies comparing patients with chronic pain and healthy controls. Specifically, we investigated a broad range of measures of brain structure as well as specific alterations in gray matter and cortical thickness. A total of 7849 abstracts of experiments published between January 1, 1990, and April 26, 2021, were identified from 8 databases and evaluated by 2 independent reviewers. Overall, 103 experiments with a total of 5075 participants met the preregistered inclusion criteria. After correction for multiple comparisons using the gold-standard family-wise error correction ( P < 0.05), no significant differences associated with chronic pain were found. However, exploratory analyses using threshold-free cluster enhancement revealed several spatially distributed clusters showing structural alterations in chronic pain. Most of the clusters coincided with regions implicated in nociceptive processing including the amygdala, thalamus, hippocampus, insula, anterior cingulate cortex, and inferior frontal gyrus. Taken together, these results suggest that chronic pain is associated with subtle, spatially distributed alterations of brain structure.